(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
The aim of the study was to evaluate the effect of ambient temperatures on sperm production in the domestic cat. Adult male cats (n=19) aged 2-5 years belonging to the reproductive colony of Cátedra de Reproducción Animal, FCV, UNLP were used. Tomcats were maintained under a controlled artificial illumination schedule to preserve sperm production but were exposed to natural environmental temperature and humidity for 18 months. Data related to daily temperature and humidity were supplied by the Department of Seismology and Meteorological Information, FCAG, UNLP. Considering the temperature requirements for the welfare of cats and sampling day temperature, ejaculates were divided into 3 groups; G1) ambient temperature >25ºC; G2) 20-22ºC; and G3) <17ºC. Results showed a significant decreased in sperm quality comparing G1 with G2 and G3. Ambient temperatures above 25ºC mainly affected concentration and total sperm quantity, showing reductions of 69 and 64% respectively. While, motility, velocity, volume, and sperm morphology decreased about 18-25%. This study provides novel information on the relationship between sperm production and environmental temperature in the domestic cat.